2016
DOI: 10.1038/ncomms12383
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the plant receptor-like kinase TDR in complex with the TDIF peptide

Abstract: In plants, leucine-rich repeat receptor-like kinases (LRR-RKs) perceive ligands, including peptides and small molecules, to regulate various physiological processes. TDIF, a member of the CLE peptide family, specifically interacts with the LRR-RK TDR to inhibit meristem differentiation into tracheary elements, and promotes cell proliferation. Here we report the crystal structure of the extracellular domain of TDR in complex with the TDIF peptide. The extracellular domain of TDR adopts a superhelical structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 34 publications
4
56
0
2
Order By: Relevance
“…RPK2 contains two island domains that map to the N-terminal and central portions of its LRR domain, but their function is unknown (63,106,114). By contrast, most of the characterized peptide ligand LRR-RKs, such as HAESA, TDR/PXY, FLS2, and PEPR, do not contain island-domain structures (89,100,120,122,144). This suggests that plants may have evolved island-domain-containing LRR ectodomains to facilitate the specific binding of relatively small ligands.…”
Section: C)mentioning
confidence: 95%
See 1 more Smart Citation
“…RPK2 contains two island domains that map to the N-terminal and central portions of its LRR domain, but their function is unknown (63,106,114). By contrast, most of the characterized peptide ligand LRR-RKs, such as HAESA, TDR/PXY, FLS2, and PEPR, do not contain island-domain structures (89,100,120,122,144). This suggests that plants may have evolved island-domain-containing LRR ectodomains to facilitate the specific binding of relatively small ligands.…”
Section: C)mentioning
confidence: 95%
“…The LRR-RKs CLAVATA 1 (CLV1), BARELY ANY MERISTEM 1-3 (BAM1-3), RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2), and TRACHEARY ELEMENT DIFFERENTIATION FACTOR RECEPTOR/PHLOEM INTERCALATED WITH XYLEM (TDR/PXY) sense small, posttranslationally modified CLV3/EMBRYO SURROUNDING REGION (ESR)-RELATED (CLE) peptide hormones, including CLV3, to maintain plant stem cell populations in the shoot and in the root (24,30,32,33,45,88,89,106,114,145). A family of secreted peptide hormones with structural similarities to CLEs, the INFLORESCENCE DEFICIENT IN ABSCISSION-LIKE (IDL) peptides, trigger abscission and cell separation processes in plants by binding to the LRR-RKs HAESA and HAESA-LIKE 2 (HSL2) (15,67,100,126).…”
Section: Architecture Of Plant Receptor Kinases (Rks) Receptor-like mentioning
confidence: 99%
“…The residues effected in these mutants are highly conserved among related LRR-RKs and structural and biochemical studies with PXY/TDIF receptor ligand pair have shown that these residues direct ligand binding [2428]. In contrast, clv1 null mutants are significantly weaker [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently two papers have reported the structural studies of TDIF-TDR(PXY) interactions. In addition, structure-guided mutational studies in both reports have indicated a conserved binding mode between CLE peptides and their cognate LRR-RLK receptors centered on residue G6 of CLEs [27, 28]. However, further studies are entailed in order to understand the binding specificities of CLE ligands to different LRR-RLKs.…”
Section: Introductionmentioning
confidence: 99%